Handbook of Industrial Waste Treatment (Marcel Dekker, 1992)
This handbook emphasizes in-depth presentation of environmental pollution sources, waste characteristics, control technologies, mangement strategies, facility innovations, process alternatives, costs, case histories, effluent standards, and future trends for each industrial or commercial operation.